Republic of Congo : Request for a Three-Year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2022)
A new wave of the COVID-19 pandemic is creating headwinds for the nascent economic recovery from the deep recession spurred by the pandemic's onset and related oil price shocks. Over the medium term, reforms supporting improved governance, economic diversification, and resilience will help confront challenges from climate change, and the global transition to low-carbon economies-gradually resulting in improved incomes, job creation, inequality, and exit from fragility. In the near term, fiscal space to address these challenges is limited. Although debt sustainability was recently restored, large liquidity risks and vulnerabilities remain. Due to arrears and on-going negotiations with an external commercial creditor, debt is classified as "in distress". The recent AIV consultation concluded on September 24, 2021.